A Parallel Domain Decomposition Algorithm for Simulating Blood Flow with Incompressible Navier-Stokes Equations with Resistive Boundary Condition (Communications in Computational Physics, 2020)
We introduce and study a parallel domain decomposition algorithm forthe simulation of blood flow in compliant arteries using a fully-coupled system ofnonlinear partial differential equations consisting of a linear elasticity equation andthe incompressible Navier-Stokes equations with a resistive outflow boundary condition. The system is discretized with a finite element method on unstructured movingmeshes and solved by a Newton-Krylov algorithm preconditioned with an overlapping restricted additive Schwarz method. The resistive outflow boundary conditionplays an interesting role in the accuracy of the blood flow simulation and we provide anumerical comparison of its accuracy with the standard pressure type boundary condition. We also discuss the parallel performance of the implicit domain decompositionmethod for solving the fully coupled nonlinear system on a supercomputer with a fewhundred processors.